DESAIN RUMAH BUDAYA PASAR GEDHE HARDJONAGORO SEBAGAI DESTINASI PARIWISATA KOTA SOLO - Ariyanto, Ahmad Fajar (Institut Seni Indoensia Surakarta, 2018)
This article is the research result of Interior Design Pasar Gedhe Hardjonagoro: Tourism Destination that Represents Cultural House in Solo City. This research is about an effort in rehabilitation program to maintain cultural heritage building that function as Traditional Market with the best featured products. The zoning and grouping are not well planned that it causes problems to the hierarchy of space. TheÂ circulation provides less accessibility for visitors, traders, distribution of goods, and waste. The research uses descriptive analytic method and design approach as design solution. The results achieved are: The concept of interior design revitalization of Pasar Gede Hardjonagoro aims to re-mapping the needs of interior design patterns for traders and visitors and provide an alternative offer of a functional, attractive design that resulting in increase of sales ratio. To achieve this goal, the design idea refers to functional, effective and efficient aspects that aesthetically adopt some architectural elements of Pasar Gede Hardjonagoro as a thematic approach.Â Keywords: Pasar Gedhe Hardjonagoro Revitalization, Tourism Destination, functional design, Cultural House.